Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{9x^2}{11y^2}:\frac{6x}{11y}=\frac{9x^2}{11y^2}\cdot\frac{11y}{6x}=\frac{3xy}{2}\)
b) \(\frac{x^2-49}{x-7}+x-2=\frac{\left(x-7\right)\left(x+7\right)}{x-7}+x-2=x+7+x-2=2x+5\)
c) \(\frac{3}{x+3}+\frac{1}{x-3}-\frac{18}{9-x^2}\)
= \(\frac{3\left(x-3\right)}{\left(x-3\right)\left(x+3\right)}+\frac{1\left(x+3\right)}{\left(x-3\right)\left(x+3\right)}-\frac{18}{\left(3-x\right)\left(x+3\right)}\)
= \(\frac{3x-9}{\left(x-3\right)\left(x+3\right)}+\frac{x+3}{\left(x-3\right)\left(x+3\right)}+\frac{18}{\left(x-3\right)\left(x+3\right)}\)
= \(\frac{3x-9+x+3+18}{\left(x-3\right)\left(x+3\right)}\)
= \(\frac{4x+12}{\left(x-3\right)\left(x+3\right)}\)
= \(\frac{4\left(x+3\right)}{\left(x-3\right)\left(x+3\right)}=\frac{4}{x-3}\)(đk: \(x-3\ne0\)=> \(x\ne3\))
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{30x^3}{11y^2}.\frac{121y^5}{25x}=\frac{6x^2.11y^3}{5}=\frac{66x^2y^3}{5}\)
b) \(\frac{x+3}{x^2-4}.\frac{8-12x+6x^2-x^3}{9x+27}=\frac{x+3}{\left(x-2\right)\left(x+2\right)}.\frac{\left(2-x\right)^3}{9\left(x+3\right)}\)
\(=\frac{-\left(x-2\right)^2}{9\left(x+2\right)}\)
p/s: chúc bạn học tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
Điều kiện: \(\hept{\begin{cases}3\left(x+y\right)\ne0\\x^2-2xy+y^2\ne0\\6\left(x+y\right)\ne0\end{cases}\Rightarrow}\hept{\begin{cases}x+y\ne0\\\left(x-y\right)^2\ne0\\x+y\ne0\end{cases}\Rightarrow\hept{\begin{cases}x\ne-y\\x\ne y\end{cases}}}\)
\(\frac{2x^3-2y^3}{3x+3y}:\frac{x^2-2xy+y^2}{6x+6y}\)
\(=\frac{2\left(x^3-y^3\right)}{3\left(x+y\right)}.\frac{6\left(x+y\right)}{\left(x-y\right)^2}\)
\(=\frac{2\left(x-y\right)\left(x^2+xy+y^2\right)}{3\left(x+y\right)}.\frac{6\left(x+y\right)}{\left(x-y\right)^2}\)
\(=\frac{4\left(x^2+xy+y^2\right)}{x-y}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
DK: \(x\ne0;y\ne0\)
\(\left(\frac{x^2-y^2}{6x^2y^2}\right):\left(\frac{x+y}{3xy}\right)=\left(\frac{\left(x-y\right)\left(x+y\right)}{6x^2y^2}\right).\left(\frac{3xy}{\left(x+y\right)}\right)=\frac{x-y}{2xy}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(6x^2+6\)
\(=6\left(x^2+1\right)\)
b) \(2x^2-18\)
\(=2\left(x^2-9\right)\)
\(=2\left(x-3\right)\left(x+3\right)\)
c) \(3x^2-3xy+4x-4y\)
\(=\left(3x^2-3xy\right)+\left(4x-4y\right)\)
\(=3x\left(x-y\right)+4\left(x-y\right)\)
\(=\left(3x-4\right)\left(x-y\right)\)
a) \(\left(x^3-9x^2+27x-27\right)\)\(:\)\(\left(x-3\right)\)
\(=\left(x-3\right)^3\)\(:\)\(\left(x-3\right)\)
\(=\left(x-3\right)^2\)
c) \(\frac{x^2-4}{2x}:\frac{3x-6}{6}\)
\(=\frac{\left(x-2\right)\left(x+2\right)}{2x}.\frac{6}{3\left(x-2\right)}\)
\(=\frac{\left(x+2\right)}{x}\)
\(\frac{9x^2}{11y^2}:\frac{3x}{2y}:\frac{6x}{11y}=\frac{9x^2}{11y^2}.\frac{2y}{3x}.\frac{11y}{6x}=\frac{18y^3x^2}{66x^2y^2}=\frac{3y}{11}\)